The use of problem structuring methods to explore the functioning and management of a selected NGO - Anyogu, Alexander A (Department of Statistical Sciences, 2014)
Poverty eradication is one of the major challenges facing South Africa and the rest of the continent. Concern around poverty alleviation in South Africa encompasses lack of capacity as well as inefficiency in the management and administration of poverty alleviation projects. Therefore, poverty alleviation agencies ought to be mindful of the issues that could affect their organizational efficiency, especially issues around organizational management. Addressing issues of management amongst the poverty alleviation agencies is necessary to assist role players in the implementation of efficient and effective poverty alleviation programs. The research explored issues around the management structure of a selected non-government organisation (SHAWCO). The objective was to develop a shared understanding of the organizational structure, amongst the members of the management team, and identify (if any) inefficiencies within the structure of the organisation. Problem Structuring Methods have been identified as a collection of tools that assist decision makers in addressing complex societal problems, and seek to alleviate or improve situations characterized by uncertainty, conflict and complexity. The study used Problem Structuring Methods to investigate the possible difficulties SHAWCO is facing as a result of management inefficiency. Interviews were used to uncover issues around the functioning and management of the organization, and an interactive problem structuring workshop was later conducted to develop a shared understanding of the identified issues.